Benign Osteoid-Producing Bone Lesions: Update on Imaging and Treatment - Trotta, Brian; Fox, Michael G. (Seminars in Musculoskeletal Radiology, 2013)
Benign osteoid-producing osseous tumors are frequently encountered in a typical musculoskeletal radiology practice. Enostoses are extremely common, but osteomas, osteoid osteomas, and osteoblastomas are diagnosed less often. A thorough discussion of the typical clinical presentation, histology, imaging findings, treatment and prognosis for each tumor is provided, with particular emphasis on more current imaging techniques and treatments.
Keywords: osteoma; enostosis; osteoblastoma; osteoid osteoma